(untitled) (Research, Society and Development, 2023)
Arterial hypertension (AH) is defined as the chronic elevation of blood pressure (BP) above 139/89 mmHg in adults. It is a frequently asymptomatic condition and usually progresses with structural and/or functional changes in organs such as the heart, being the main reversible factor for cardiovascular diseases. The aim of the present study was to develop an Educational manual as a facilitator of blood pressure self-measurement (AMPA) in the control of hypertensive patients with heart disease. Thirty-seven hypertensive and heart disease patients attended at the Integrated Center for Diabetes and Hypertension in Fortaleza participated in the study. All of them used the manual and the usability was later evaluated using the System Usability Scale (SUS), translated into Portuguese as the Escala de Usabilidade do Sistema, based on the degree of agreement according to the Likert scale. Acceptability was measured using the Technology Acceptance Model originally formulated by Davis. Regarding the usability questionnaire with the SUS scale, the mean total score obtained was 78.78±11.66, being the usability considered excellent, as well as the acceptability, which obtained a final score of 96.08 ± 5, 67. It can be concluded that the manual demonstrated excellent usability and acceptability on the part of those investigated, which proves its importance for blood pressure control, having favorable characteristics to be a tool aimed at helping the patient to better understand his pathology and the correct way to measure blood pressure.